Boiling incipience of subcooled water flowing in a narrow tube using wavelet analysis. (5th March 2018) - Shibahara, M.; Fukuda, K.; Liu, Q.S.; Hata, K.; Masuzaki, S.
Highlights: Incipient boiling phenomena of subcooled water in a narrow tube were observed. The boiling signal was analyzed by the wavelet decomposition method. The semi-empirical correlation of the boiling incipience was obtained. Abstract: Various incipient boiling phenomena for subcooled water flowing in a uniformly heated narrow tube were observed experimentally. The boiling signal was analyzed using the wavelet decomposition method. The boiling incipience of subcooled water in the narrow tube was recorded by a sound level meter at various flow velocities. A platinum tube was used as the experimental tube with an inner diameter of 1.0 mm. The length of the experimental tube was 23.2 mm. The tube was heated by the Joule effect using a direct current. The inlet temperature and flow velocities ranged 285–346 K and 2.5–14 m/s, respectively. The surface superheat ascended with an increase of the heat flux until the incipient boiling point was reached. The initial temperature overshoot did not appear as the outlet pressure increased. Since the existing correlations underestimated the incipient heat flux, a semi-empirical correlation of the boiling incipience was obtained based on the experimental data. The predicted value of the new correlation is in agreement with the experimental data within ±30%.